Effective counseling: A major challenge of tuberculosis control programme in tackling the dual disease burden of tobacco consumption among tuberculosis in India - Nehal; Shyamala Krishnaswamy Kothandapani; Bidhata Khatri; Supriya Tiwari (Indian Journal of Respiratory Care, 2020)
Background: Tuberculosis (TB) and tobacco are the major public health problems with high morbidity and mortality. Tobacco consumption is the most common modifiable risk factor associated with TB infection, relapse, and recurrence. This study aimed at estimating the prevalence of tobacco consumption patterns among patients with TB and assessing effectiveness of counseling and tobacco cessation intervention. Patients and Methods: A cross-sectional prospective study was conducted in patients with TB (pulmonary and extrapulmonary), ≥18 years registered under Revised National TB Control Program (RNTCP) (Directly Observed Treatment, Short-course), at a tertiary care hospital, South India, from January 2018 to June 2018. Relevant clinical data was collected. Participants were interviewed about tobacco consumption, and counseling was offered to these patients and willingness to quit tobacco usage was assessed using 5A and 5R's approach. Results: Of the total 125 patients, 40 of them were tobacco users (smoking and oral tobacco) with a prevalence of 32%. Mean age was 38 ± 2 years. Tobacco consumption was significantly high (19.2%) in the 31–50 years age group (P = 0.04) with an increased association among pulmonary TB. Majority of the tobacco users were male (38.96%), predominantly smokers (31.16%) and female patients were oral tobacco users (20.83%). With effective counseling, 60% of tobacco users were willing to quit tobacco gradually, while 27.5% were willing to quit abruptly and avail pharmacotherapy. Conclusion: There is high prevalence of tobacco usage among TB patients. Majority of males were smokers. Females were predominantly oral tobacco users. Implementing strategies for effective counseling and tobacco cessation intervention, in coordination with RNTCP would have greater impact on treatment outcome.